Differentiated thyroid cancer (Consensus and dissent in the 2001)) - Peyroulou, Alfredo (Cirugía del Uruguay, 2002)
It is difficult to refer to thyroid cancer in general form, since that term is being encompassed to a set of biological entities, which constitutes a real challenge for surgeons rich in controversy